A comparative evaluation of retrievability of three different obturating systems using protaper universal rotary retreatment files: An in vitro cone-beam computed tomography analysis - Shrija Paradkar; Khushboo Goyal; Suparna Ganguly Saha; Anuj Bhardwaj; Mainak Kanti Saha; Amit Singh Nirwan (Endodontology, 2022)
Aim: The aim of this in-vitro study was to comparatively evaluate the ease of retreatment in canals, obturated through GuttaFlow 2, GuttaCore, and conventional Lateral compaction technique using ProTaper Universal Retreatment (PTUR) Files. Materials and Methods: Sixty single-rooted mandibular premolars were selected and the canals were instrumented with ProTaper Universal rotary files up to size #F3. Samples were randomly divided into three experimental groups of 20 teeth each and obturated using three different obturating systems (GROUP I-Lateral compaction technique, GROUP II-GuttaFlow 2, GROUP III-GuttaCore). All the groups underwent cone-beam computed tomography (CBCT) analysis following which retrieval of the previous root canal filling was done using the PTUR files. Post retreatment CBCT images were used to assess the amount of remaining obturating material at varying depths (3 mm, 6 mm, and 12 mm) for all three groups. Statistical analysis was performed using repeated measures analysis of variance and ANOVA. Results: Irrespective of the obturating system used, filling material could not be removed completely from the root canal walls. Significantly more amount of obturating material was observed in the apical third than the middle third and coronal third of the root canal space (P < 0.05). When comparing the groups, the maximum percentage of remaining obturating material was seen in Group III (GuttaCore) followed by Group I (lateral compaction), with the least being observed in Group II (GuttaFlow2). Conclusion: The GuttaCore technique utilizing carrier-based gutta-percha had the maximum amount of remaining obturating material after retreatment when compared to the GuttaFlow2 and Lateral Compaction techniques.